2021
DOI: 10.1016/s2214-109x(21)00346-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of typhoid conjugate vaccine in Nepal: final results of a phase 3, randomised, controlled trial

Abstract: Background Typhoid fever is a major public health problem in low-resource settings. Vaccination can help curb the disease and might reduce transmission. We have previously reported an interim analysis of the efficacy of typhoid conjugate vaccine (TCV) in Nepali children. Here we report the final results after 2 years of follow-up. MethodsWe did a participant-masked and observer-masked individually randomised trial in Lalitpur, Nepal, in which 20 019 children aged 9 months to younger than 16 years were randomly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 21 publications
5
51
0
Order By: Relevance
“…71,72 New data available from the two-year follow-up of the randomized-controlled trial in Nepal revealed a protective efficacy against blood-culture confirmed typhoid fever of 79.0% (95% CI, 61.9-88.5%). 73 These results were comparable to those from the interim analysis, which collectively indicate long-term vaccine protection and provide further support for its use in typhoid-endemic regions. Further, results also showed that the Vi-TT-TCV performed consistently well across different regions, populations and transmission settings with a robust safety profile.…”
Section: Typhoid Vaccines: Recent Developmentssupporting
confidence: 75%
“…71,72 New data available from the two-year follow-up of the randomized-controlled trial in Nepal revealed a protective efficacy against blood-culture confirmed typhoid fever of 79.0% (95% CI, 61.9-88.5%). 73 These results were comparable to those from the interim analysis, which collectively indicate long-term vaccine protection and provide further support for its use in typhoid-endemic regions. Further, results also showed that the Vi-TT-TCV performed consistently well across different regions, populations and transmission settings with a robust safety profile.…”
Section: Typhoid Vaccines: Recent Developmentssupporting
confidence: 75%
“…Fields trials have since been underway in countries with high burden of disease and/or high rates of antimicrobial resistance ( Neuzil et al, 2020 ). Recently, the result of an efficacy of Vi-TT vaccine in Nepal was reported ( Shakya et al, 2021 ). The field trial enrolled 20,019 children aged 9 months to 16 years who received a single dose of TCV or capsular group A meningococcal conjugate vaccine (MenA).…”
Section: Evaluation Of Typhoid Vaccine Candidates Using Chimmentioning
confidence: 99%
“…The field trial enrolled 20,019 children aged 9 months to 16 years who received a single dose of TCV or capsular group A meningococcal conjugate vaccine (MenA). The group reported a protective efficacy of 79% against blood culture confirmed typhoid fever at 2 years ( Shakya et al, 2021 ). Similar results were observed in children participating in a large field study in Bangladesh ( Qadri et al, 2021 ).…”
Section: Evaluation Of Typhoid Vaccine Candidates Using Chimmentioning
confidence: 99%
“…A single dose of Typbar-TCV ® , the first prequalified Vi conjugate, was 79–95% effective in preventing typhoid fever following immunization of infants, children, and young adults. 5 10 However, even if high vaccination coverage substantially reduces the incidence of typhoid, 5 10 for some years chronic S. Typhi carriers will remain within the population constituting a reservoir of infection that can be transmitted. Ideally, chronic carriers can be systematically identified (by stool culture and IgG Vi antibody titer) and treated if the antimicrobial susceptibility of the endemic strain(s) allows.…”
Section: Introductionmentioning
confidence: 99%